Accessibility and availability of reproductive health care services at primary health centre level and association with health outcome in Aspirational Districts of India - Tapan Debnath; Bhupen Barman; Krishna Barman; Ranjan Roy (Elsevier, 2023)
Background: This study concerns the reproductive health care of women of reproductive age in the selected Aspirational districts in India. This paper mainly aims to identify the level of accessibility and availability of reproductive health care and their interlinking with the health outcomes in terms of institutional delivery and percentage of women who received any Antenatal Check-up. Study design: This is a cross sectional study. Methods: A composite index has been constructed at the district level for every indicator (accessibility, availability, and health outcome) to identify the level of accessibility and availability and to analyse the association between accessibility, availability, and health outcomes using the Pearson chi-square test and ternary diagram. The thematic maps used for showing the disparities of indicators in the selected Aspirational districts. Results: After developing the composite index for accessibility and availability of health care, it is shown that the districts which ranked in accessibility, not ranked in availability of health care. The study reveals that the overall composite index for ranking the districts in terms of accessibility and availability, closely associated with the health outcomes. Accessibility and availability are also associated with the health outcome of reproductive health in Aspirational districts in India. Accessibility of health care services is more significant for better health outcomes than the availability of health care services in the Aspirational districts in India. Conclusion: Accessibility and availability are the component for access to health care and influence the health outcome.